Biomechanical analysis of saving motion for soccer goalkeepers focused on the function of lower extremities - Numazu, N.; Fujii, N. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to clarify the function of the lower extremities during the saving motion of a goal keeper (GK). Eleven male university GKs dived toward a ball thrown 3.5 m ahead. Three-dimensional (3D) coordinates and ground reaction forces were obtained with a 3D motion capture system (250 Hz) and 2 force platforms (1000 Hz). The novel findings in this study are summarized as follows: (1) hip extension of the contralateral side leg to the ball is an important motion in the Pre phase and (2) exertion of extension torque at the hip in the early Transition phase has an important role for controlling backward leaning of the thigh during the saving motion.